Golden Reflection - Abdul Razak, Muhammad Umar
The UiTM Law program under the School of Administration and Law welcomed its first Law students in 1968. It was a small group of students registering for the LL.B (University of London) External program as well as the English Bar at Law program. Since then it has metamorphosed into its own with its unique home grown programmes in Law, making it one of Malaysia's notable professional graduate faculties. Today, fifty years on, it is one of the well-known public law schools in Malaysia, home to more than 11,000 alumni, who have among them become leaders in the legal profession across Malaysia. This Coffee Table book, Golden Reflections is to celebrate this milestone, commemorating 50 years of teaching, learning, growing from strength to strength, sharing the historical path with a collection of photographs and profiles based on essential themes that characterize our Law School's history and values: people-centred, community engaged, justice-seeking, dynamic, and inclusive.